Moderasi Beragama : Mengenal Ratib Saman Sebagai Sebuah Tradisi Keagamaan Pada Tariqat Naqsabandiyah Di Desa Besilam, Kec.Padang Tualang, Kab. Langkat - Suharno, Muhammad Iqbal; Situmorang, Jauharah Jilan; Putri, Mega Amelia; Tanjung, Alwi Fajri; Rokan, Mustapa Khamal (Universitas Pahlawan Tuanku Tambusai, 2024)
Tradition or custom reflects actions that are repeatedly performed in a similar manner, indicating the performer's affinity for such actions. This study examines a relevant religious tradition, namely the Ratib Saman Tradition. This tradition is closely associated with the Naqshbandiyah Sufi order, which has spread widely throughout the Nusantara. The focus of this discussion is directed towards the implementation of this tradition in the Besilam or Babussalam area, a region in North Sumatra known for its strong religious atmosphere. The research methodology adopts a qualitative and descriptive approach to analyze the phenomenon of the Ratib Saman Tradition within the socio-religious context of the Besilam community. The research results are expected to provide an in-depth understanding of the significance and dynamics of religious traditions within society, particularly in the context of the Naqshbandiyah Sufi order in North Sumatra. Keywords: Tradition, Ratib Samman, Besilam, Tariqat naqsabandiyah